Manganese clusters of aromatic oximes: synthesis, structure and magnetic properties. Issue 39 (16th September 2016) - Chen, Zilu; Hu, Zhaobo; Li, Yisheng; Liang, Yuning; Wang, Xinyu; Ouyang, Li; Zhao, Qin; Cheng, Haiyan; Liang, Fupei
Abstract : The reported five manganese clusters with different skeletons reveal the contribution of parent rings, non-coordinating groups and anions on structural variation. Abstract : With the aim of tuning the structures by using oxime ligands with different non-coordinating groups, three aromatic oxime ligands were designed by fusing oxime groups (N–OH) onto different non-coordinating groups. Their reactions with the corresponding Mn(ii ) salts gave five manganese clusters [MnIII3(μ3 -O)(L 1 )3 (DMF)(H2 O)3 Cl]·2DMF·CH3 OH (1 ), [MnIII3(μ3 -O)(L 2 )3 (OAc)(CH3 OH)2 ] (2 ), [MnIII6(μ3 -O)2 (L 2 )6 (H2 O)(py)7 ](ClO4 )2 ·py·0.5CH3 OH·2H2 O (3 ), [MnIII8O4 (L 2 )8 (DMF)4 ]·DMF·6CH3 CN (4 ), and [MnII4MnIII4O4 (L 3 )12 ]·3DMF·6H2 O (5 ), in which H2 L 1, H2 L 2 and HL 3 represent indane-1, 2, 3-trione-1, 2-dioxime, acenaphthenequinone dioxime, and 9, 10-phenanthrenedione-9-oxime, respectively. Their structures were determined and studied in detail.1 and2 show planar triangular trinuclear MnIII3 structures.3 has a hexanuclear MnIII6 skeleton formed from two MnIII3 triangular units through inter-trinuclear mutual coordination.4 and5 present octanuclear skeletons constructed from planar triangular Mn3 O and tetrahedral Mn4 O secondary building units, respectively, with different symmetries and different oxidation states of the manganese ions. Their structural studies reveal a significant contribution of the parent rings for fusing oxime groups, different non-coordinating groups and anions to the formation of different cluster skeletons. Their magnetic properties were investigated and simulated, which revealed the presence of dominant antiferromagnetic interactions between the metal ions in these compounds.